Boosting the Performance of Solid‐State Lithium Battery Based on Hybridizing Micron‐Sized LATP in a PEO/PVDF‐HFP Heterogeneous Polymer Matrix. Issue 9 (4th August 2020) - Xue, Xilai; Zhang, Xiangxin; Liu, Yongchuan; Chen, Sujing; Chen, Yuanqiang; Lin, Junhong; Zhang, Yining
Abstract : Solid‐state poly(ethylene oxide) (PEO) electrolyte exhibits a low ionic conductivity at ambient conditions, and large interfacial resistance between PEO and electrodes obstructs its applications in lithium metal batteries. Heterogeneous solid electrolytes (HSEs) are an alluring solution for the exploitation of PEO. Herein, PEO/poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP)/micron‐sized Li1.4 Al0.4 Ti1.6 (PO4 )3 (LATP) heterogeneous solid electrolytes are originally prepared to decrease the crystallinity of PEO and interfacial resistance between HSEs and electrodes. Heterogeneous solid electrolyte composed of PEO/PVDF‐HFP/5% micron‐sized LATP (PPL‐5) exhibits superior electrochemical properties in ionic conductivity (3.01 × 10 −5  S cm −1 ), lithium transference number (0.55) at 30 °C, and a broad potential window (5.31 V). Li/PPL‐5/Li symmetric cell displays a relatively stable potential response during 800 h cycling, authenticating long‐term compatibility between the as‐prepared electrolyte and lithium metal. LiFePO4 (LFP) is used as a cathode to test the chemical and electrochemical stability of PPL‐5. The discharge capacity of LFP/PPL‐5/Li coin cell maintains 97.9 mAh g −1 at 0.8 C after 500 cycles with capacity retention of 86.7%. Such excellent performance of PPL‐5 can be ascribed to the reduction of crystallinity of PEO and the improvement of the interfacial contact between electrolyte and electrodes, when PVDF‐HFP and micron‐sized LATP are simultaneously incorporated with PEO electrolyte. Abstract : A hybrid solid electrolyte based on poly(ethylene oxide) (PEO)/poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP)/micron‐sized Li1.4 Al0.4 Ti1.6 (PO4 )3 (LATP) is prepared by a facile solution‐casting method and it exhibits outstanding electrochemical performance including comparatively high ionic conductivity, lithium transference number, and wide electrochemical window. The solid‐state battery composed of LiFePO4, PEO/PVDF‐HFP/5 wt% LATP, and Li displays a long cycle life and relatively high charge–discharge capacity.